2021
DOI: 10.1007/s10113-021-01830-x
|View full text |Cite
|
Sign up to set email alerts
|

Twentieth century temperature and snow cover changes in the French Alps

Abstract: Changes in snow cover associated with the warming of the French Alps greatly influence social-ecological systems through their impact on water resources, mountain ecosystems, economic activities, and glacier mass balance. In this study, we investigated trends in snow cover and temperature over the twentieth century using climate model and reanalysis data. The evolution of temperature, precipitation and snow cover in the European Alps has been simulated with the Modèle Atmospherique Régional (MAR) applied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 64 publications
1
14
0
1
Order By: Relevance
“…Nevertheless, we found that NbS addressing snow cover reduction are located where changes will be lower in summer than across the Alps. This is because they refer to three enabling NbS that focus on ski resorts at higher altitudes that are less affected by snow cover change during winter but with higher change during summer (Beaumet et al 2021). While our database is not exhaustive, the relatively small number of initiatives identified for ski resorts adaptation is consistent with previous syntheses showing limited nature-based interventions from the skiing sector, which still mainly invests in snowmaking solutions (Berard-Chenu et al 2021).…”
Section: Nature-based Solutions Are Distributed Across a Range Of Cli...supporting
confidence: 77%
“…Nevertheless, we found that NbS addressing snow cover reduction are located where changes will be lower in summer than across the Alps. This is because they refer to three enabling NbS that focus on ski resorts at higher altitudes that are less affected by snow cover change during winter but with higher change during summer (Beaumet et al 2021). While our database is not exhaustive, the relatively small number of initiatives identified for ski resorts adaptation is consistent with previous syntheses showing limited nature-based interventions from the skiing sector, which still mainly invests in snowmaking solutions (Berard-Chenu et al 2021).…”
Section: Nature-based Solutions Are Distributed Across a Range Of Cli...supporting
confidence: 77%
“…However, ref. 62 and ref. 63 revealed some large scale differences in temperature and precipitation trends between S2M analyses and the Regional Climate Model, MAR, forced by ERA20C reanalysis at the boundaries but not assimilating any observation inside the simulation domain.…”
Section: Methodsmentioning
confidence: 86%
“…Similarly, the increase in the relative frequency of snowmelt‐deficit droughts at the cost of cold‐snow‐season droughts (Figure 4) may explain the observed increase in drought deficits, which are comparably high for snowmelt‐deficit droughts. The increase in the relative frequency of snowmelt‐droughts is likely related to an increase in the snow line and a decrease in snow depth—both a consequence of climate change (Beaumet et al., 2021; Matiu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%